PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI KECAMATAN TANDES KOTA SURABAYA - Eka Yunayka, Siti (Seminar Nasional Manajemen, 2025)
This study aims to determine the effect of work environment and work motivation on employee performance at Tandes District, Surabaya City. The research sample consisted of 54 employees. The research method used a quantitative approach with SEM-PLS analysis. The results showed that the work environment did not significantly affect employee performance, while work motivation had a positive and significant effect. These findings highlight the importance of improving work motivation to enhance employee performance in public service institutions